Influence of roughness of wood on adhesion of polyurethane wood finish - Jevtic, Petronije; Temelkova, Anastasija (FDTME-Skopje, 2017)
Surface properties of wood condition direct its application in many areas. The surface roughness depends on the factors that can be controlled through the way and regime of processing and also by factors that can be controlled. According to the anatomical wood structure there are several types of roughness. For the surface treatment process, the most important operation is grinding, since the surface, prepared at that stage of treatment, is immediately processed by liquid and solid materials. The aim of the study of this paper is to establish the dependence between the roughness of the massive tree wood surface, formed in various surface preparation types, and adhesion of the polyurethane colorless lacquer
Keywords: roughness, processing, grinding, adhesion